Economic Growth and Global Economic Ties in the Epoch of Global Turbulence: Trends and Problems - D. Krasochenkov (Международная аналитика, 2018)
In the paper an attempt is made to summarize the factors and trends characteristic of the functioning and development of the world economy and international economic relations under the conditions of slowing down the globalization pace and growing dependence of foreign trade and investment on geopolitical processes. An analysis of key macroeconomic indicators of national development and interstate relations has been employed as a basis for exploring the general context of the development of the world economy. The strategic contours are also determined of Russia's effective participation in the system of world economic relations at the stage of global economic turbulence.